Asymptotic behavior of the eigenvalues of a boundary-value problem for a second-order elliptic operator-differential equation - Aliev, B. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study the asymptotic behavior of the eigenvalues of a boundary-value problem with spectral parameter in the boundary conditions for a second-order elliptic operator-differential equation. The asymptotic formulas for the eigenvalues are obtained.